2023
DOI: 10.1007/s11695-023-06532-3
|View full text |Cite
|
Sign up to set email alerts
|

How Good is Stratification and Prediction Model Analysis Between Primary and Revisional Roux-en-Y Gastric Bypass Surgery? A Multi-center Study and Narrative Review

Abstract: Introductions Revision surgery because of weight recurrence is performed in 2.5–33% of primary vertical banded gastroplasty (VBG), laparoscopic sleeve gastrectomy (LSG), and gastric band (GB) cases. These cases qualify for revisional Roux-en-Y gastric bypass (RRYGB). Methods This retrospective cohort study analyzed data from 2008 to 2019. A stratification analysis and multivariate logistic regression for prediction modeling compared the possibility of suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
2
3
0
Order By: Relevance
“…Although not statistically significant, LAGB revisions had nearly significant higher TWL outcomes compared to SG revisions (TWL 24.1% vs 16.5%; p = 0.08). This is similar to previous reports on revisions after LAGB and SG-with SG revisions trailing LAGB revisions regarding weight loss outcomes [17,19]. TWL < 20% was considered a poor clinical response and this was seen in 30% of patients which is reasonable when considering it from the revision date and in our opinion is only one of the markers determining the outcome postoperatively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although not statistically significant, LAGB revisions had nearly significant higher TWL outcomes compared to SG revisions (TWL 24.1% vs 16.5%; p = 0.08). This is similar to previous reports on revisions after LAGB and SG-with SG revisions trailing LAGB revisions regarding weight loss outcomes [17,19]. TWL < 20% was considered a poor clinical response and this was seen in 30% of patients which is reasonable when considering it from the revision date and in our opinion is only one of the markers determining the outcome postoperatively.…”
Section: Discussionsupporting
confidence: 90%
“…Our study suggests that RBS is associated with a reasonable complication rate in the elderly population. We had only three patients with significant complications (CD > = 3) (7.7%), which is similar to the complication rates reported in previous reports on revisional bariatric surgeries on younger candidates [17]. Although patients s/p SG undergoing revisional surgery had a 12.5% major complication rate compared to 4.3% in s/p LAGB, this did not reach statistical significance due to the small sample size, in addition it is difficult to draw clear conclusions from this relatively small cohort.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, in a recent study, rOAGB showed significantly higher %EWL than rLSG at 2 (70.4% vs. 55.6%) and 4 years (68.7% vs. 54.6%) [ 31 ]. A 2023 study [ 32 ] delineated a noticeable difference between primary RYGB and revisional RYGB post-LAGB, with significantly lower %EWL (93.7 vs. 64.1%) and %TWL (47.3% vs. 24.6%) after 2 years. However, it is to be noted that this outcome was exclusively observed in revisional RYGB procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Revisional RYGB is commonly employed to revise bariatric procedures due to insufficient WL or weight recurrence. However, despite this, only one third of all the patients undergoing revisional surgery had a sufficient %EWL after 2 years compared with primary RYGB [11].…”
Section: Introductionmentioning
confidence: 93%
“…BS is considered a successful intervention when the outcome of the surgery is the loss of ≥50% of the percentage of excess weight (%EWL), which is related to decreasing the risk of developing obesity-related diseases [5]. This index is widely used, even in recent studies [6][7][8][9][10], including reviews on this topic [11][12][13], to analyse the efficacy of bariatric surgery on weight loss. However, there is still a high percentage of failure (up to 50%), since the efficacy of the procedure depends on many factors, such as type of procedure, age, sex and ethnic background [14].…”
Section: Introductionmentioning
confidence: 99%